CT and US findings in a rarely seen case of cardiac echinococcosis: A case report - (:unkn) unknown (Springer-Verlag, 1993)
Both Computed Tomography (CT) and Ultrasonography (US) are highly sensitive methods for detecting cardiac cysts. Pericardial cysts, ventricular aneurysms and hydatid cysts, especially in endemic areas must be considered in the differential diagnosis. In this report, we present the CT and US findings of a pathologically-proven myocardial hydatid cyst. There are no pathognomonic US or CT signs of cardiac echinococcosis. However, when a cardiac cyst is detected, examination of the liver by US or CT together with the history may give clues in the differential diagnosis and may save the patient's life. © 1993 Springer-Verlag.
Keywords: Computed tomography; Echinococcosis; Heart; Ultrasonography